Green–Light–Driven Poly(N-isopropylacrylamide-acrylamide)/Fe3O4 Nanocomposite Hydrogel Actuators - Cao, Ying; Li, Wenjiao; Quan, Fengyu; Xia, Yanzhi; Xiong, Zhong (Frontiers in Materials, 2022)
Light-responsive hydrogel actuators show attractive biomedical applications for in vivo drug delivery tool, surgical tissue repair operation and vascular cleaning, due to its non-contact, rapid, precise and remote control by light. Conventional visible-light responsive hydrogels contain special chemical structure or groups and the difficulty in synthesis results in that few can be applied to fabricate visible-light-driven hydrogel actuators. In this study, based on photothermal effect, surface-modified Fe3O4 nanoparticles were incorporated into poly(N isopropylacrylamide-acrylamide) hydrogel by UV photopolymerization, which revealed excellent green-light-responsive volume change. Under a laser irradiation of 200 mW at 520 nm, the bending angle deformation of hydrogel strips with 2.62 wt% Fe3O4 reached 107.8°. Strip-shaped hydrogel actuator could be applied to transport tiny objects. Further, a boomerang-like hydrogel actuator was designed and fabricated to drive a floating foam on water. By 12 cycles of continuous laser on-off irradiation to a hydrogel actuator underwater, a circular returning movement of the float was accomplished. The study on driving a float using visible-light-triggered hydrogel actuators provides a new idea for the design of light-driven biomedical devices and soft robots.